Ecomomic evaluation of urban amenities including the effects on migration - Komei Sasaki; Takeshi Tomioka (European Regional Science Association (ERSA), 2002)
In contrast to static equilibrium model of Roback type (1982), this paper presents a dynamic system for evaluating urban amenities where urban population size as well as wage income and land price is endogenously determined.The model was applied to the data on 208 cities in Kanto and Tohoku regions(northern area in Japan), and on the basis of the estimation results,the value of urban amenities was calculated. The empirical analysis indicated that nealy one-third of inter-city migration is explained by the inter-city differences in the value of urban amenities.
Keywords: 330